The effect of weightlifting training with added respiratory dead space on buffering capacity and blood lactate in weightlifters - Vahid Rabiei; Mohammad Fashi (Shahid Beheshti University, 2024)
Background and Purpose: Improvements in performance based on buffering capacity has been of great interest, where beneficial effects have been reported by using added respiratory dead space (ADRS) in endurance training. However, the use of ADRS in resistance training has not been investigated. The aim of this study was to investigate the effects of added respiratory dead space in weightlifting training on carbon dioxide, bicarbonate, and blood lactate.Materials and Methods: Eighteen young healthy males (age, 28.72±14.14 years and body mass index 24.27±1.34 kg/m2) with at least 6 months experience of weightlifting training, were voluntarily selected and randomly divided into two groups of weightlifting+added respiratory dead space (WARDS, n = 9) and weightlifting training (n = 9). Both groups performed selected weightlifting training three sessions per week in the first to fourth weeks, four sessions per week in the fifth to sixth weeks and five sessions per week in the seventh to tenth weeks at an intensity corresponding to 80% of one-repetition maximum and rate of perceived exertion (RPE) 14 to 16. However, the WARDS group were breathing through a device that increased respiratory dead space volume to 1200-ml during the training. The anthropometric measurements and blood samples were taken before and after the first and last training session to determine carbon dioxide, HCO3- and lactate levels. For between-group comparisons repeated measures of ANOVA with between-group subjects was used.Results: No significant difference was observed between the two groups for body mass index (P=0.510), body weight (P=0.714) and body fat percentage (P=0.942). Changes in the CO2 (P=0.045) and lactate (P≥0.001) levels were significantly different in the mask group compared to non-mask group. No significant difference was observed between the two groups for HCO3- (P=0.947). As a result of comparing the responses of training variables, there was a significant increase in CO2 only after the last training session (P=0.019), while, lactate increased after the first and the last training session (P=0.001) and HCO3- after the first session (P=0.029) and the last training session (P=0.045) in the training group with mask.Conclusions: Using an added respiratory dead space with a volume of 1200 ml during weightlifting training is a simple method to improve buffering capacity and increase lactate tolerance. Weightlifting training sessions are not considered more difficult with this strategy and can provide an alternative to well-known training protocols, and athletes can benefit from the adaptations in various directions such as hypertrophy, performance improvement.